Literasi Keuangan: Pelatihan Penggunaan Aplikasi Akuntansi Berbasis Android dalam Menyusun Laporan Keuangan - Segarawasesa, Fajar Satriya (Rahmatan Lil 'Alamin Journal of Community Services, 2024)
This activity aims to overcome the problems faced by MSME business actors at the Kemantren Kraton Yogyakarta. Every MSME business player has the same problem, namely a lack of understanding of financial literacy, especially in preparing MSME financial reports and financial management. This has the impact of not separating personal financial records from their business. As a result, businesspeople have difficulty assessing whether their business results are making a profit or a loss. To overcome this problem, a financial literacy program was formed in the form of training on the use of Android-based accounting applications in preparing financial reports. This program was selected due to its user-friendly interface and seamless compatibility with smartphones, making it easy to download and use. The approach to carrying out tasks include providing instruction and support for using the program. The outcomes of this endeavor exhibited a favorable reaction from the individuals involved. Nevertheless, according to the assessment findings, it is important to consistently do this activity, taking into account the time constraints for mentoring. Certain participants still need more coaching.